Elemental Uptake by Calcite Slowly Grown From Seawater Solution: An in-situ Study via Depth Profiling - Gabitov, Rinat; Sadekov, Aleksey; Yapaskurt, Vasiliy; Borrelli, Chiara; Bychkov, Andrey; Sabourin, Kaitlyn; Perez-Huerta, Alberto (Frontiers in Earth Science, 2019)
Crystal growth rate has not been sufficiently explored to understand element partitioning between calcite and seawater solutions. We investigated the uptake of Li, B, Mg, Sr, and Ba by Mg-bearing calcite slowly grown on a calcite cleavage fragment. Experiments were conducted by elevating the alkalinity of an artificial seawater solution. Growth rates were evaluated by addition of lanthanum spike. At the end of each experiment, cleavage fragments were extracted and examined with micro-Raman spectroscopy, scanning electron microscopy (SEM), electron backscattered diffraction (EBSD), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) using depth profiling technique. Distribution of Li, B, Mg, Sr, and Ba in calcite overgrowth as well as partition coefficients of those elements were evaluated.